Strategies for strengthening SME resilience during the covid-19 pandemic through banana processed product innovations - Maula, Kholida Atiyatul; Mubarokah, Isro'iyatul; Azizah, Ani Nurdiani (Community Empowerment, 2021)
SMEs were the sector most affected during the Covid-19 pandemic. Among them are SMEs in Tegallega Village, Ciampel District, Karawang Regency. The problems faced are very diverse, such as decreasing demand, inaccessible additional capital, no cost to continue the business, low technology usage ability, poor marketing, lack of product innovation, and absence of records and books. The problem-solving method used was training in developing human resources in the field of entrepreneurship, mentoring home industry groups, as well as monitoring and evaluation. The results achieved in this activity were providing training to SME actors to be able to take advantage of the abundant resources, namely bananas. Banana fruit can be used as raw material because it is easy to find and the price is relatively cheap and can be processed with a variety of more innovative variations, such as banana caramel, Super Banana Chocolate Cake, and banana stick.